Biomedical applications of organoids in genetic diseases - Huang Wenhua; Jeong Seogsong; Kim Won; Chen Lei (Medical Review)
Organoid technology has significantly transformed biomedical research by providing exceptional prospects for modeling human tissues and disorders in a laboratory setting. It has significant potential for understanding the intricate relationship between genetic mutations, cellular phenotypes, and disease pathology, especially in the field of genetic diseases. The intersection of organoid technology and genetic research offers great promise for comprehending the pathophysiology of genetic diseases and creating innovative treatment approaches customized for specific patients. This review aimed to present a thorough analysis of the current advancements in organoid technology and its biomedical applications for genetic diseases. We examined techniques for modeling genetic disorders using organoid platforms, analyze the approaches for incorporating genetic disease organoids into clinical practice, and showcase current breakthroughs in preclinical application, individualized healthcare, and transplantation. Through the integration of knowledge from several disciplines, such as genetics, regenerative medicine, and biological engineering, our aim is to enhance our comprehension of the complex connection between genetic variations and organoid models in relation to human health and disease.